COMPARATIVE ANALYSIS OF SMALL MOLECULES AND NATURAL PLANT COMPOUNDS AS THERAPEUTIC INHIBITORS TARGETING RdRp AND NUCLEOCAPSID PROTEINS OF SARS COV 2: AN IN SILICO APPROACH - POLEBOYINA, PAVAN KUMAR; PAWAR, SMITA C (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Coronavirus disease 2019 (COVID-19) is a virus-borne infection caused by the severe acute respiratory syndrome coronavirus disease-2 (SARS-CoV-2) virus. Nucleocapsid protein and RNA-dependent RNA polymerase (RdRp) activity in viral structural membrane, transcription, and replication have been identified as desirable targets for the development of novel antiviral strategies. The SARS-COV-2 N protein binds to the viral genome to promote the precise folding of the hammerhead ribozyme, preventing ineffective RNA confirmations, and directs them into a helical capsid shape or ribonucleoprotein complex, which is vital for viability. RNA synthesis requires RdRp to form phosphodiester bonds based on the RNA template. SARS-CoV-2 RNA synthesis, transcription, and replication depend on RdRp’s complex with nsp7 and nsp8. Methods: Our study targeted SARS-COV-2 RdRp and N proteins with natural plant compounds and small molecules. Hyperchem software optimized their structures geometrically and energetically. Based on MolDock, Rerank, and H-bonding energy, the best ligands were selected using the Molegro virtual docker. Results: In our analysis, we have identified nine compounds against N protein and seven compounds against RdRp protein that had more potent inhibitory effects with the lowest MolDock scores. The top 6 (Alpha solanine, Betanin, cairicoside I, Ginsenoside rb 1, Naringin, Polyphyllin I) compounds that have better inhibitory effects against both proteins. Conclusion: We conclude that the top six compounds have greater inhibitory efficacy against N and RdRp protein than other compounds. However, in vitro and in vivo experimental studies, as well as clinical trials, are required to achieve the desired result.